2005
DOI: 10.1016/j.visres.2004.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The watercolor effect: Quantitative evidence for luminance-dependent mechanisms of long-range color assimilation

Abstract: When a dark chromatic contour delineating a figure is flanked on the inside by a brighter chromatic contour, the brighter color will spread into the entire enclosed area. This is known as the watercolor effect (WCE). Here we quantified the effect of color spreading using both color-matching and hue-cancellation tasks. Over a wide range of stimulus chromaticities, there was a reliable shift in color appearance that closely followed the direction of the inducing contour. When the contours were equated in luminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
95
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(117 citation statements)
references
References 34 publications
20
95
1
Order By: Relevance
“…For example, while relatively large chromaticity shifts of 38.11% and 18.04% were needed for the two narrowest columns (5.4 and 9.3 min of arc, respectively), shifts of only 4.61% and 1.75% were required for wider columns. Note that the magnitude of the effect for a stimulus width of 1.43 deg is similar to that found by Devinck et al (2005) under comparable conditions. We conclude that the WCE is most salient for stimuli with smaller enclosed areas.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…For example, while relatively large chromaticity shifts of 38.11% and 18.04% were needed for the two narrowest columns (5.4 and 9.3 min of arc, respectively), shifts of only 4.61% and 1.75% were required for wider columns. Note that the magnitude of the effect for a stimulus width of 1.43 deg is similar to that found by Devinck et al (2005) under comparable conditions. We conclude that the WCE is most salient for stimuli with smaller enclosed areas.…”
Section: Resultssupporting
confidence: 80%
“…They were asked to adjust the chromaticity of the enclosed stimulus area until it appeared achromatic (hue cancellation). The results of an earlier study (Devinck et al 2005) showed no difference between color-matching and hue-cancellation tasks for the pattern used in the present paper. In addition, observers generally found the hue-cancellation task to be easier than matching and were able to perform this task relatively quickly.…”
Section: Methodscontrasting
confidence: 46%
See 2 more Smart Citations
“…Based on pilot experiments we assumed that the illusory color could be matched by a color located in color space on the straight line connecting the background white with the color of the orange line of the watercolor pattern. A recent study published after the present results were submitted confirmed this assumption (Devinck et al, 2005). A set of 20 comparison colors distributed along that line was used.…”
Section: Measuring the Illusory Colorsupporting
confidence: 55%